Clinical Manifestation of Cardiac Rupture in Patients with ST-Segment Elevation Myocardial Infarction: Early Versus Late Primary Percutaneous Coronary Intervention - Xile Bi; Bin Wang; Gary Tse; Cuilian Dai; Xiang Chen; Fanqi Meng; Yan Wang (Ubiquity Press, 2022)
Background: Cardiac rupture is one of the fatal complications of ST-Segment Elevation Myocardial Infarction (STEMI) in the primary percutaneous coronary intervention (PPCI) era. The present study aims to identify risk factors of cardiac rupture among patients suffering from STEMI, treated with early and late PPCI. Methods: This is a multicenter retrospective cohort study involving STEMI patients with cardiac rupture (CR group), matched with STEMI patients without CR (control group) in a 1:5 ratio. They were divided into the early (≤ 6 h) and the late (> 6 h) PCI groups. Multivariable logistic regression was utilized to identify risk factors for cardiac rupture. Results: Seventy-four patients in the CR and 370 in the control group were included. Multivariable regression identified lateral infarction (OR = 11.89, 95% CI 2.22-63.81, p < 0.01) in the early PCI phase as a significant risk factor for cardiac rupture. Thrombolysis in myocardial infarction (TIMI) grade 0-1 (early PCI: OR = 4.16, 95% CI 1.33-13.0, p = 0.01; late PCI: OR = 4.46, 95% CI 1.59-12.54, p < 0.01) was a risk factor for both early and late PCI groups. In contrast, TIMI grade 2 was associated with a higher rupture risk within the late (OR = 16.87, 95% CI 3.83-74.19, p < 0.001) but not for the early (OR = 5.44, 95% CI 0.76-39.07, p = 0.09) PCI groups. STEMI combined with Killip IV was associated with a higher rupture risk for the late PCI group (OR = 1.43, 95% CI 1.03-1.99, p = 0.04). Intra-aortic balloon pump (IABP) was protective against cardiac rupture within early PPCI (OR = 0.18, 95% CI 0.04-0.89, p = 0.04). In contrast, glycoprotein IIb/IIIa inhibitors were associated with lower rupture risks in both the early and late groups (early PCI: OR = 0.38, 95% CI 0.17-0.87, p = 0.02; late PCI: OR = 0.33, 95% CI 0.15-0.75, p < 0.01). Conclusions: No reflow or slow blood flow is associated with a higher risk of cardiac rupture in early and late PCI patients. Glycoprotein IIb/IIIa inhibitors are beneficial in preventing heart rupture, and the use of IABP in early PPCI is also helpful in preventing heart rupture.